2017
DOI: 10.1016/j.apergo.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Neck and upper extremity pain in sonographers – Associations with occupational factors

Abstract: Sonographers have a high risk of musculoskeletal disorders. This study explores the associations between working conditions and musculoskeletal pain based on the frequency and intensity of pain in the neck and upper extremities. A questionnaire was answered by 291 female sonographers. High prevalence of neck/shoulder pain was associated with eye complaints and headache related to work on the computer, dissatisfaction with the computer workstation, high mechanical exposure index (MEI) and high demands. The poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 41 publications
1
24
1
Order By: Relevance
“…Echocardiography is highly sensory demanding, requiring mental focus and control of body movements [13] . This is similar to the cases of dentists and air traffic controllers, who have also been found to experience WRMSDs [33] , [34] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Echocardiography is highly sensory demanding, requiring mental focus and control of body movements [13] . This is similar to the cases of dentists and air traffic controllers, who have also been found to experience WRMSDs [33] , [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Most echocardiographers also perform other sonographic examinations, for example, vascular examinations, and nonsonographic tasks, for example, spirometry. It has been shown that those who perform echocardiography have a higher prevalence of elbow/hand pain than those who only perform other sonographic examinations [13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they are exposed to occupational risk factors such as unnatural postures, repetitive movements, and load handling, and prior research has demonstrated the relationship between these risk factors and the occurrence of painful musculoskeletal syndromes [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Sonographers as professional health care providers have reported a high prevalence of workrelated musculoskeletal pain and discomfort [12,13]. Some latest studies indicated the high prevalence of neck and shoulder pain among female sonographers [14,15]. Other researchers also studied the stress-related risk factors such as disproportionate workload, time pressure, tough or difficult tasks, insufficient rest breaks, monotony in conducting the same tasks, and the physically poor work environment conditions are considered as additional factors affecting health care professionals [16].…”
Section: Introductionmentioning
confidence: 99%